Development of E-Modules Integrated Game-Based Learning Method for Illustration Drawing to Enhance Student Understanding - Zhitfi, Gyska; Iriaji (IJESS International Journal of Education and Social Science, 2025)
The teaching of fine arts, particularly illustration drawing for eighth-grade students at SMPN 03 Lawang, highlights the necessity for developing innovative media integrated with more interactive teaching methods. This need arises due to indications of students' limited comprehension of the subject matter. This research focuses on developing an e-module combined with a game-based learning approach to optimize the learning process of illustration drawing. This research aims to assess the need for enhancing students' understanding of illustration drawing concepts, describe the outcomes of developing an e-module integrated with game-based learning, and evaluate its effectiveness, validity, and feasibility. The method used in this study is the research & development method with the Four-D model. This research approach combines qualitative and quantitative methods with trial subjects involving teachers, students, and experts. The results obtained from the expert validator on the media aspect showed a figure of 91%, and the results of the material aspect validator got a figure of 86%, both of which are included in the very valid category. The feasibility test by the art and culture teacher reached a score of 94%, and the results of the feasibility test by students reached a score of 94%, also in the very valid category. Meanwhile, the comparison test of pre-test and post-test by students showed a score of 0.777, in the effective category. Therefore, it was decided that the media developed was valid and feasible to be used to improve the understanding of eighth-grade students of SMP Negeri 03 Lawang.